Deep Eutectic Solvent Compatible Metallic Catalysts: Cationic Pyridiniophosphine Ligands in Palladium Catalyzed Cross‐Coupling Reactions. Issue 7 (10th March 2017) - Marset, Xavier; Khoshnood, Abbas; Sotorríos, Lia; Gómez‐Bengoa, Enrique; Alonso, Diego A.; Ramón, Diego J.
Abstract: Cationic pyridiniophosphine ligands have been synthetized in an attempt to develop a deep eutectic solvents (DESs) compatible catalytic systems. These ligands, in combination with PdCl2, have been successfully applied to different palladium‐catalyzed cross coupling reactions, such as Suzuki–Miyaura, Sonogashira, or Heck couplings. While traditional palladium ligands in DES medium failed to reproduce the results obtained in VOC solvents, these cationic phosphines improved the catalytic activity of palladium as no other traditional ligand could in such a polar medium. In addition, the recyclability of these processes was studied, allowing us to reuse both, catalyst and solvent up to 5 times in Suzuki and Sonogashira reactions without a significant drop in the catalytic activity. Regarding the structure of the Pd catalysts, titration, NMR, and DFT studies have clearly demonstrated the coordination properties of the DES‐compatible cationic phosphine ligands. Abstract : Truly madly deeply ! Cationic pyridiniophosphine ligands have been synthetized for a general deep eutectic solvent (DES) compatible catalytic system. These ligands, in combination with PdCl2, have been successfully applied to different cross coupling reactions. These cationic phosphines improved the catalytic activity of palladium as no other traditional ligand could in such polar media. The catalyst and solvent could be recycled up to 5 times without depletion of yields.